Characteristics of Hypoglycemic Diabetic Patients Visiting the Emergency Room - Tong Min Kim; Hyunah Kim; Seung-Hwan Lee; Jae-Hyoung Cho; Hyunyong Lee; Hyeon Woo Yim; Kun-Ho Yoon; Hun-Sung Kim (Cardiovascular Therapeutics)
Introduction. Severe hypoglycemia can be life-threatening; therefore, it is important to identify the characteristics of the hypoglycemic patients. The aim of this study is to analyze the type and characteristics of diabetic patients with hypoglycemia who visited an emergency room. Methods. We included diabetic patients with hypoglycemia who visited the emergency room of St. Mary’s Hospital in Seoul from January 2009 to August 2018 in the study. Hypo_S group patients visited the emergency room once whereas Hypo_M group patients visited twice or more. We also compared the incidence of cardiovascular disease between the groups within 5 years after hypoglycemia. Results. A total of 843 patients were included in this study, with a mean age of 71±14 years and average glycated hemoglobin (HbA1c) level of 6.7±1.4%. For patients with hypoglycemia, lower body mass index, lower HbA1c, shorter diabetes duration, and lower glomerular filtration rate have a statistically significant relationship with patient characteristics in the emergency room group (all p<0.001). Hypoglycemia symptoms were most frequently observed between 6:00 and 12:00 am (p<0.001). Cardiovascular diseases within 5 years after discharge were more frequent in the Hypo_S group than in the Hypo_M group; however, there was no statistical significance. The frequency of aneurysms was significantly higher in patients with hypoglycemia than in other patients in the emergency room (p<0.05). Conclusion. Relatively thin older patients with a diabetes duration shorter than 10 years and good blood sugar control showed higher frequency of visits to the emergency room due to hypoglycemia. For these patients, medical staff should always be mindful of their susceptibility to hypoglycemia when prescribing insulin or OHA and educate them on the prevention of hypoglycemia.